(TiCrMoNbTa) C series high-entropy ceramic and preparation method thereof
By introducing carbon vacancy into the high entropy carbide system and using vacuum hot press sintering technology, the problem of high entropy ceramics is solved, and the effect of preparing high-performance high-entropy ceramics at low temperatures is achieved.
Patent Information
- Application Number
- CN202411975515.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The sintering temperature of high entropy carbide ceramics is usually above 2000°C. High sintering temperature limits its application, and low-temperature sintering methods need to be developed to achieve the preparation of high entropy ceramics.
By introducing carbon vacancy into the high-entropy carbide system, a single-phase face-centered cubic high-entropy carbide ceramic with non-stoichiometric ratio was prepared, and the sintering temperature was sintered at 1650°C using vacuum hot press sintering technology to reduce the sintering temperature.
It effectively reduces the sintering temperature of high-entropy ceramics, improves the density and performance of the material, and achieves the goal of preparing high-performance high-entropy ceramics at low temperatures.
Smart Images

Figure CN119753472A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high entropy ceramic material preparation, and specifically relates to a (TiCrMoNbTa) C series high entropy ceramic and a preparation method thereof. Background Art
[0002] Transition metal carbides have high melting points, corrosion resistance, excellent mechanical properties and physical and chemical stability. They have been widely used in industries such as aerospace fuels, nuclear fuels and special refractory materials. However, as the development of traditional materials is getting closer and closer to their intrinsic limits, the existing material system can no longer meet the growing needs of new technologies in various industries. In order to respond to the demand for new materials under increasingly complex conditions, the concept of "high entropy ceramics" has been introduced from high entropy alloys, further expanding the scope of transition metal carbide ceramic material systems. With the application of the concept of high entropy to the field of ceramics, high entropy ceramics have become a hot topic of research. High entropy ceramics have high melting points, high thermal conductivity, good thermal stability, excellent corrosion resistance and electrochemical properties, etc., and have great development space and application prospects. However, the sintering temperature of high entropy carbide ceramics is usually above 2000℃. The high sintering temperature greatly limits its application. It is urgent to develop a method to sinter high entropy ceramics at low temperatures. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a low-carbon (TiCrMoNbTa) C-based high-entropy ceramic and a preparation method thereof. By introducing carbon vacancies into the high-entropy carbide system, a non-stoichiometric single-phase face-centered cubic high-entropy carbide ceramic is prepared, which is beneficial to the diffusion and homogenization of various elements and effectively reduces the sintering temperature of the high-entropy ceramic. The prepared high-entropy carbide ceramic has a higher density and excellent performance.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0005] A low-carbon (TiCrTaNbMo)C high-entropy ceramic, wherein the (TiCrMoNbTa)C high-entropy ceramic is a single-phase face-centered cubic structure, and the raw material powder comprises the following compounds: Ti, TiC, Cr3C2, Mo2C, NbC, and TaC.
[0006] A further improvement of the technical solution of the present invention is that it comprises the following steps:
[0007] S1: mixing five kinds of carbide raw material powders evenly to obtain mixed powder A;
[0008] S2: uniformly mixing the metal Ti powder and the mixed powder A to obtain a mixed powder B;
[0009] S3: Through vacuum hot pressing sintering technology, the mixed powder B is placed in a graphite mold with good thermal conductivity, and solid phase reaction sintering is carried out in a hot pressing sintering furnace to obtain a low-carbon non-stoichiometric high entropy ceramic (TiCrMoNbTa) C system.
[0010] A further improvement of the technical solution of the present invention is that the particle size of the raw material powder Ti is 45μm, the particle size of TiC is 3-5μm, the particle size of Mo2C is 2-3μm, the particle size of TaC is 1-3μm, the particle size of NbC is 5-10μm, and the particle size of Cr3C2 is 5-10μm, and the purity of each raw material powder is higher than 99.5%.
[0011] A further improvement of the technical solution of the present invention is that the specific steps of step S1 are:
[0012] S11: weighing each raw material carbide powder according to an equal metal atomic ratio;
[0013] S12: Put the raw material powder weighed in S11 into an agate ball mill, with a ball-to-powder ratio of 10:1 and a mass ratio of large balls to small balls of 1:1. Use vacuum silicone grease to seal the ball mill, and fill the ball mill with argon gas;
[0014] S13: ball milling is performed using a planetary ball mill with a rotation speed of 240 r / min and a ball milling time of 10 h.
[0015] A further improvement of the technical solution of the present invention is that: the raw material powders in step S1 are prepared according to the atomic ratio of metals, and the ratio of each raw material powder is TiC:NbC:Cr3C2:Mo2C:TaC=6:6:2:3:6
[0016] A further improvement of the technical solution of the present invention is that the specific steps of step S2 are:
[0017] S21: adding different contents of metal Ti single substance powder to powder A;
[0018] S22: Put the raw material powder weighed in S21 into an agate ball mill, with a ball-to-powder ratio of 10:1 and a mass ratio of large balls to small balls of 1:1. Use vacuum silicone grease to seal the ball mill, and fill the ball mill with argon gas;
[0019] S23: ball milling is performed using a planetary ball mill with a rotation speed of 240 r / min and a ball milling time of 10 h.
[0020] A further improvement of the technical solution of the present invention is that the molar content of the metal Ti single substance powder added in step S2 is 10% to 30%, the particle size of the raw material powder Ti is 45 μm, and the purity of the raw material powder is higher than 99.5%.
[0021] A further improvement of the technical solution of the present invention is that: the powder is mixed by two-step ball milling in steps S1 and S2, thereby preventing the occurrence of cold welding.
[0022] A further improvement of the technical solution of the present invention is that graphite paper is provided on the inner wall of the S3 graphite mold and at the position in contact with the powder.
[0023] The further improvement of the technical solution of the present invention is that: the solid phase reaction sintering process of step S3 first adopts a pre-pressure of 10 MPa, then gradually increases the pressure, and adopts a pressure maintenance of 30 MPa. During the sintering process, the vacuum degree of the graphite mold is always kept below 1.8×10 -2 Pa.
[0024] A further improvement of the technical solution of the present invention is that the sintering temperature in step S3 is 1650° C., the heating rate of the sintering process is 10° C. / min, and the holding time is 2 h.
[0025] Due to the adoption of the above technical solution, the technical progress achieved by the present invention is:
[0026] The (TiCrMoNbTa)C series high entropy ceramics prepared by the present invention have high density, high hardness and high application value. Metal Ti single substance powder and carbide powder with different molar contents are selected for blending and sintering, and a high concentration of carbon vacancies is introduced into the high entropy carbide system to prepare non-stoichiometric low-carbon high entropy carbide ceramics, which is beneficial to the diffusion and homogenization of various elements, effectively reduces the sintering temperature of the high entropy ceramics, and the prepared high entropy ceramics have excellent mechanical, physical and chemical properties.
[0027] The present invention prepares non-stoichiometric high-entropy carbide ceramics by combining Ti powder and carbide powder with different molar contents, thereby introducing carbon vacancies and effectively improving the diffusion coefficient of the material, so that the material has a stronger material transmission ability than the stoichiometric ceramic material, reduces the sintering temperature, promotes the densification of the non-stoichiometric high-entropy carbide ceramic, and finally forms a single-phase solid solution. The prepared high-entropy ceramics have excellent mechanical, physical and chemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a comparative XRD spectrum of the mixed powders prepared in Example 2 of the present invention and Comparative Example 2;
[0029] Figure 2 is the XRD spectrum of the (TiCrMoNbTa) C-based high entropy ceramic prepared in Example 2 of the present invention;
[0030] Figure 3 is a SEM image of the (TiCrMoNbTa) C-based high entropy ceramic prepared in Example 2 of the present invention;
[0031] Figure 4 is an EDS image of the (TiCrMoNbTa) C-based high entropy ceramic prepared in Example 2 of the present invention;
[0032] Figure 5 is a SEM image of the (TiCrMoNbTa) C-based high entropy ceramic prepared in Example 3 of the present invention;
[0033] Figure 6 is an EDS image of the (TiCrMoNbTa) C-based high entropy ceramic prepared in Example 3 of the present invention;
[0034] Figure 7 is the XRD spectrum of the (TiCrMoNbTa) C-based ceramic with equal molar ratio prepared in Comparative Example 1 of the present invention;
[0035] Figure 8 It is a hardness diagram of the (TiCrMoNbTa) C-based high entropy ceramics prepared in three embodiments of the present invention and comparative example 1. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with embodiments:
[0037] A method for preparing a (TiCrMoNbTa)C series high entropy ceramic comprises the following steps:
[0038] S1, preparing mixed powder A;
[0039] S11: weighing the raw material powders according to equal metal atomic ratios, the raw material powders are TiC powder, Cr3C2 powder, Mo2C powder, NbC powder, and TaC powder, and the purity of each powder is higher than 99.5%; the particle size of the raw material powder TiC is 3-5μm, the particle size of Mo2C is 2-3μm, the particle size of TaC is 1-3μm, the particle size of NbC is 5-10μm, and the particle size of Cr3C2 is 5-10μm;
[0040] S12: Put the raw material powder weighed in S11 into an agate ball mill with a ball-to-powder ratio of 10:1, seal the ball mill with vacuum silicone grease, and fill the ball mill with argon gas;
[0041] S13: ball milling is performed using a planetary ball mill with a rotation speed of 240 r / min and a ball milling time of 10 h.
[0042] S2, preparing mixed powder B;
[0043] S21: Mixing the mixed powder A with metal Ti powders with different contents, wherein the molar ratio of the added metal Ti is 10% to 30%, the purity of the raw material powder Ti is higher than 99.5%, and the particle size is 45 μm;
[0044] S22: The raw material powder weighed in S21 is placed into an agate ball mill with a ball-to-powder ratio of 10:1, the ball mill is sealed with vacuum silicone grease, and argon gas is filled into the ball mill;
[0045] S23: ball milling is performed using a planetary ball mill with a rotation speed of 240 r / min and a ball milling time of 10 h.
[0046] S3. Preparation of non-stoichiometric high entropy ceramics (TiCrMoNbTa) C series by vacuum hot pressing
[0047] Place the mixed powder B into a graphite mold with good thermal conductivity, and wrap the inner wall of the graphite mold and the position in contact with the powder with graphite paper. Place the graphite mold in a vacuum hot pressing sintering furnace and evacuate it to a pressure below 1.8×10 -2 Pa; the sintering temperature is set to 1650℃, the heating rate is 10℃ / min, and during the sintering process, the sintering furnace first uses a pre-pressure of 10MPa, and then gradually increases the pressure. When the temperature rises to the sintering temperature of 1650℃, the pressure is controlled to 30MPa and kept warm for 2h. The prepared non-stoichiometric (TiCrMoNbTa) C-based high entropy carbide ceramics are all single-phase face-centered cubic structures.
[0048] Embodiment 1:
[0049] A low-carbon non-stoichiometric high-entropy ceramic, wherein the non-stoichiometric high-entropy ceramic is a single-phase face-centered cubic structure, and the atomic percentage expression is (Ti 0.28 Cr 0.18 Mo 0.18 Nb 0.18 Ta 0.18 )C 0.75 .
[0050] A method for preparing the low-carbon non-stoichiometric high-entropy ceramic comprises the following steps:
[0051] S1. Preparation of mixed powder A
[0052] Select the required mixed powder: prepare the initial powder TiC powder, Cr3C2 powder, Mo2C powder, NbC and TaC powder, weigh 20g according to the atomic ratio of metals, and the molar ratio is TiC: NbC: Cr3C2: Mo2C: TaC = 6: 6: 2: 3: 6. Use a balance to weigh 2.30g TiC powder, 2.31g Cr3C2 powder, 3.92g Mo2C powder, 4.04g NbC powder and 7.43g TaC powder, respectively, place these powders in an agate ball mill, add 200g agate balls according to the ball-to-powder ratio of 10: 1, and the mass ratio of large balls to small balls is 1: 1. To prevent the mixed powder from being oxidized, fill the ball mill with argon gas, and put the agate ball mill into a planetary ball mill for mixing for 10 hours at a speed of 240r / min.
[0053] S2. Preparation of mixed powder B
[0054] Select the required mixed powder: prepare the initial powder Ti powder and the mixed powder A prepared in step S1, weigh 20g according to the weight ratio, the molar ratio content of Ti powder is 10%, and the atomic ratio content of powder A is 90%. Use a balance to weigh 0.97g Ti powder and 19.03g mixed powder A respectively, place these powders in an agate ball mill, add 200g agate balls at a ball-to-powder ratio of 10:1, and the mass ratio of large balls to small balls is 1:1. To prevent the mixed powder from being oxidized, fill the ball mill with argon gas, and put the agate ball mill into a planetary ball mill for mixing for 10h at a speed of 240r / min.
[0055] S3, vacuum hot pressing sintering preparation of high entropy ceramics (Ti 0.28 Cr 0.18 Mo 0.18 Nb 0.18 Ta 0.18 )C 0.75
[0056] Place the mixed powder B into a graphite mold with good thermal conductivity, and wrap the inner wall of the graphite mold and the position in contact with the powder with graphite paper. Place the graphite mold in a vacuum hot pressing sintering furnace and evacuate it to a pressure below 1.8×10 -2 Pa. The sintering temperature was set at 1650℃, the heating rate was 10℃ / min, and the temperature was kept at 600℃, 900℃, and 1250℃ for 10min respectively during the heating process. During the sintering process, the sintering furnace first used a pre-pressure of 10MPa, and then gradually increased the pressure. When the temperature reached 1650℃, the pressure was controlled to 30MPa and kept warm for 2h.
[0057] After the sintering process is completed, the sintering furnace is cooled and the sample is taken out after reaching room temperature. The round cake-shaped product is cut by wire cutting according to the required size for subsequent experiments. 0.28 Cr 0.18 Mo 0.18 Nb 0.18 Ta 0.18 )C 0.75 The Vickers hardness of ceramic is 2241HV 0.5 . Prepared (Ti 0.28 Cr 0.18 Mo 0.18 Nb 0.18 Ta 0.18 )C 0.75 High entropy ceramics have a single-phase face-centered cubic structure.
[0058] Example 2
[0059] A low-carbon non-stoichiometric high-entropy ceramic, wherein the non-stoichiometric high-entropy ceramic is a single-phase face-centered cubic structure, and the atomic percentage expression is (Ti 0.36 Cr 0.16 Mo 0.16 Nb 0.16 Ta 0.16 )C 0.66 .
[0060] A method for preparing the low-carbon non-stoichiometric high-entropy ceramic comprises the following steps:
[0061] S1. Preparation of mixed powder A
[0062] Select the required mixed powder: prepare the initial powder TiC powder, Cr3C2 powder, Mo2C powder, NbC and TaC powder, weigh 20g according to the atomic ratio of metals, and the molar ratio is TiC: NbC: Cr3C2: Mo2C: TaC = 6: 6: 2: 3: 6. Use a balance to weigh 2.30g TiC powder, 2.31g Cr3C2 powder, 3.92g Mo2C powder, 4.04g NbC powder and 7.43g TaC powder, respectively, place these powders in an agate ball mill, add 200g agate balls according to the ball-to-powder ratio of 10: 1, and the mass ratio of large balls to small balls is 1: 1. To prevent the mixed powder from being oxidized, fill the ball mill with argon gas, and put the agate ball mill into a planetary ball mill for mixing for 10 hours at a speed of 240r / min.
[0063] S2. Preparation of mixed powder B
[0064] Select the required mixed powder: prepare the initial powder Ti powder and the mixed powder A prepared in step S1, weigh 20g by weight, the molar ratio of Ti powder is 20%, and the molar ratio of powder A is 80%. Use a balance to weigh 2.06g Ti powder and 17.93g mixed powder A respectively, place these powders in an agate ball mill, add 200g agate balls at a ball-to-powder ratio of 10:1, and the mass ratio of large balls to small balls is 1:1. To prevent the mixed powder from being oxidized, fill the ball mill with argon gas, and place the agate ball mill in a planetary ball mill for mixing for 10h at a speed of 240r / min.
[0065] S3, vacuum hot pressing sintering preparation of high entropy ceramics (Ti 0.36 Cr 0.16 Mo 0.16 Nb 0.16 Ta 0.16 )C 0.66
[0066] Place the mixed powder B into a graphite mold with good thermal conductivity, and wrap the inner wall of the graphite mold and the position in contact with the powder with graphite paper. Place the graphite mold in a vacuum hot pressing sintering furnace and evacuate it to a pressure below 1.8×10 -2 Pa. The sintering temperature was set at 1650℃, the heating rate was 10℃ / min, and the temperature was kept at 600℃, 900℃, and 1250℃ for 10min respectively during the heating process. During the sintering process, the sintering furnace first used a pre-pressure of 10MPa, and then gradually increased the pressure. When the temperature reached 1650℃, the pressure was controlled to 30MPa and kept warm for 2h.
[0067] After the sintering process is completed, the sintering furnace is cooled and the sample is taken out after reaching room temperature. The round cake-shaped product is cut by wire cutting according to the required size for subsequent experiments. 0.36 Cr 0.16 Mo 0.16 Nb 0.16 Ta 0.16 )C 0.66 Ceramics have excellent performance and a hardness of about 2054HV 0.5 .
[0068] Figure 2 This is the XRD spectrum of the high entropy ceramic of Example 2, which shows a single face-centered cubic structure phase without any diffraction peaks of other phases. Figure 3 For Example 2 (Ti 0.36 Cr 0.16 Mo 0.16 Nb 0.16 Ta 0.16 )C 0.66 SEM image of high entropy ceramics. In the SEM image, there are no obvious pores and defects on the surface of the sample, indicating that (Ti 0.36 Cr 0.16 Mo 0.16 Nb 0.16 Ta 0.16 )C 0.66 High entropy ceramics have a higher density. Figure 4 For Example 2 (Ti 0.36 Cr 0.16 Mo 0.16 Nb 0.16 Ta 0.16 )C 0.66 EDS image of high entropy ceramics. In the EDS image, the five elements Ti, Cr, Mo, Nb, and Ta are evenly distributed.
[0069] Example 3
[0070] A low-carbon non-stoichiometric high-entropy ceramic, wherein the non-stoichiometric high-entropy ceramic is a single-phase face-centered cubic structure, and the atomic percentage expression is (Ti0.44 Cr 0.14 Mo 0.14 Nb 0.14 Ta 0.14 )C 0.58 .
[0071] A method for preparing the low-carbon non-stoichiometric high-entropy ceramic comprises the following steps:
[0072] S1. Preparation of mixed powder A
[0073] Select the required mixed powder: prepare the initial powder TiC powder, Cr3C2 powder, Mo2C powder, NbC and TaC powder, weigh 20g according to the atomic ratio of metals, and the molar ratio is TiC: NbC: Cr3C2: Mo2C: TaC = 6: 6: 2: 3: 6. Use a balance to weigh 2.30g TiC powder, 2.31g Cr3C2 powder, 3.92g Mo2C powder, 4.04g NbC powder and 7.43g TaC powder, respectively, place these powders in an agate ball mill, add 200g agate balls according to the ball-to-powder ratio of 10: 1, and the mass ratio of large balls to small balls is 1: 1. To prevent the mixed powder from being oxidized, fill the ball mill with argon gas, and put the agate ball mill into a planetary ball mill for mixing for 10 hours at a speed of 240r / min.
[0074] S2. Preparation of mixed powder B
[0075] Select the required mixed powder: prepare the initial powder Ti powder and the mixed powder A prepared in step S1, weigh 20g by weight, the molar ratio of Ti powder is 30%, and the molar ratio of powder A is 70%. Use a balance to weigh 3.30g Ti powder and 16.70g mixed powder A respectively, place these powders in an agate ball mill, add 200g agate balls at a ball-to-powder ratio of 10:1, and the mass ratio of large balls to small balls is 1:1. To prevent the mixed powder from being oxidized, fill the ball mill with argon gas, and place the agate ball mill in a planetary ball mill for mixing for 10h at a speed of 240r / min.
[0076] S3, vacuum hot pressing sintering preparation of high entropy ceramics (Ti 0.44 Cr 0.14 Mo 0.14 Nb 0.14 Ta 0.14 )C 0.58
[0077] Place the mixed powder B into a graphite mold with good thermal conductivity, and wrap the inner wall of the graphite mold and the position in contact with the powder with graphite paper. Place the graphite mold in a vacuum hot pressing sintering furnace and evacuate it to a pressure below 1.8×10 -2Pa. The sintering temperature was set at 1650℃, the heating rate was 10℃ / min, and the temperature was kept at 600℃, 900℃, and 1250℃ for 10min respectively during the heating process. During the sintering process, the sintering furnace first used a pre-pressure of 10MPa, and then gradually increased the pressure. When the temperature reached 1650℃, the pressure was controlled to 30MPa and kept warm for 2h.
[0078] After the sintering process is completed, the sintering furnace is cooled and the sample is taken out after reaching room temperature. The round cake-shaped product is cut by wire cutting according to the required size for subsequent experiments. x The Vickers hardness of ceramic is 2002HV 0.5 . Prepared (Ti 0.44 Cr 0.14 Mo 0.14 Nb 0.14 Ta 0.14 )C 0.58 High entropy ceramics have a single-phase face-centered cubic structure. Figure 5 is the SEM picture of Example 3, Figure 6 This is the EDS image of Example 3. In the SEM and EDS images, it is found that the Cr, Nb, Ta, and Mo elements are evenly distributed, the Ti element is enriched, and the carbon vacancy concentration has reached the limit, and further solid solution cannot be completed.
[0079] Comparative Example 1:
[0080] An equimolar ratio (Ti 0.2 Cr 0.2 Mo 0.2 Nb 0.2 Ta 0.2 )C 0.83 The method for preparing ceramics comprises the following steps:
[0081] S1: Prepare the required mixed powder:
[0082] S11: Prepare raw material powder: Select the required mixed powder: Prepare the initial powder TiC powder, Cr3C2 powder, Mo2C powder, NbC and TaC powder, weigh 20g according to the atomic ratio of metals, and the molar ratio is TiC: NbC: Cr3C2: Mo2C: TaC = 6: 6: 2: 3: 6. Use a balance to weigh 2.30g TiC powder, 2.31g Cr3C2 powder, 3.92g Mo2C powder, 4.04g NbC powder and 7.43g TaC powder respectively, place these powders in an agate ball mill, add 200g agate balls according to the ball-to-powder ratio of 10: 1, and the mass ratio of large balls to small balls is 1: 1. To prevent the mixed powder from being oxidized, fill the ball mill with argon gas, and put the agate ball mill into a planetary ball mill for mixing powder for 10 hours, with a speed of 240r / min.
[0083] S2: Vacuum hot pressing sintering with equal molar ratio (Ti 0.2 Cr 0.2 Mo 0.2 Nb 0.2 Ta 0.2 )C 0.83 ceramics:
[0084] 20g of the mixed powder prepared in S1 was placed in a graphite mold with good thermal conductivity, and graphite paper was wrapped around the inner wall of the graphite mold and the position in contact with the powder. The graphite mold was placed in a vacuum hot pressing sintering furnace and vacuumed to a pressure below 1.8×10 -2 Pa. The sintering temperature was set at 1650℃, the heating rate was 10℃ / min, and the temperature was kept at 600℃, 900℃, and 1250℃ for 10min respectively during the heating process. During the sintering process, the sintering furnace first used a pre-pressure of 10MPa, and then gradually increased the pressure. When the temperature reached 1650℃, the pressure was controlled to 30MPa and kept warm for 2h.
[0085] After the sintering process is completed, the sintering furnace is cooled and the sample is taken out after reaching room temperature. The round cake-shaped product is cut by wire cutting according to the size required for subsequent experiments. The Vickers hardness of the ceramic prepared under this process is 1893HV 0.5 .
[0086] Figure 7 The XRD spectrum of this comparative example is compared with the XRD spectrum of Example 2 of the present invention. The non-stoichiometric ratio (Ti 0.36 Cr 0.16 Mo 0.16 Nb 0.16 Ta 0.16 )C 0.66 There are no other impurity peaks, the diffraction peaks are narrow and the peak intensity is high, the crystallinity is good, and the single-phase face-centered cubic structure high entropy ceramics are successfully prepared at 1650°C. 0.2 Cr 0.2 Mo 0.2 Nb 0.2 Ta 0.2 )C 0.83 The diffraction peaks are asymmetric and contain mixed peaks, indicating that solid solution has not been well completed at 1650°C.
[0087] Comparative Example 2
[0088] This comparative example and Example 2 use the same raw material powder, except that TiC powder, Cr3C2 powder, Mo2C powder, NbC powder, TaC powder and Ti powder are weighed in the same proportion as in Example 2 and then mixed, and 200g of agate balls are added according to a ball-powder ratio of 10:1, and the mass ratio of large balls to small balls is 1:1. To prevent the mixed powder from being oxidized, argon gas is filled into the ball mill, and the agate ball mill is placed in a planetary ball mill for mixing powder for 10 hours at a speed of 240r / min.
[0089] This powder and the mixed powder B in Example 2 were subjected to X-ray diffraction.
[0090] Figure 1 The XRD spectrum of the mixed powder 1 prepared by the two-step ball milling method in Example 2 is compared with the XRD spectrum of the mixed powder 2 of the same composition obtained by the one-step ball milling in Comparative Example 2. The diffraction peak intensity of the mixed powder 1 is higher, the prepared powder particles are fine, and the diffraction peak angle is increased to a certain extent. Other compounds diffuse into the main lattice, which promotes the formation of a single-phase solid solution.
[0091] Figure 8 The hardness changes of the examples of the present invention and comparative example 1 show that as the carbon vacancy concentration increases, that is, the Ti content increases and the carbon content decreases, the Vickers hardness of the material generally shows a slight downward trend, because as the Ti content increases, the carbon vacancy concentration increases and the number of covalent bonds decreases. At the same time, the hardness of comparative example 1 is lower than that of the examples of the present invention, because comparative example 1 has not yet completed a good solid solution at 1650°C, and the crystallinity is poor.
[0092] The preferred examples of the present invention described above are mainly used to illustrate the preparation principle and specific implementation scheme of the present invention, and the purpose is to enable people familiar with this technology to understand the content of the present invention and implement it accordingly. However, the implementation of the present invention is not limited to the above-mentioned cases. Many modifications and changes can be made without departing from the scope and spirit of the present invention. These changes and improvements fall within the scope of the present invention claimed for protection. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A (TiCrMoNbTa) C-based high entropy ceramic, characterized in that: The high entropy ceramic is a single-phase face-centered cubic structure, and the raw material powder for preparing the (TiCrMoNbTa)C series high entropy ceramic includes the following simple substances and carbides: TiC, NbC, TaC, Mo2C, Cr3C2 and Ti simple substance.
2. A method for preparing (TiCrMoNbTa)C-based high entropy ceramics, characterized in that The steps include: S1: five carbide raw material powders of TiC, NbC, TaC, Mo2C, and Cr3C2 are uniformly mixed to obtain mixed powder A; S2: uniformly mixing metal Ti powders with different molar contents and mixed powder A to obtain mixed powder B; S3: Through vacuum hot pressing sintering technology, the mixed powder B is placed in a graphite mold with good thermal conductivity, and solid phase reaction sintering is carried out in a hot pressing sintering furnace to obtain a high entropy ceramic (TiCrMoNbTa) C system.
3. The method for preparing a (TiCrMoNbTa) C-based high entropy ceramic according to claim 2, characterized in that: The particle size of the raw material powder Ti is 45 μm, the particle size of TiC is 3-5 μm, the particle size of Mo2C is 2-3 μm, the particle size of TaC is 1-3 μm, the particle size of NbC is 5-10 μm, and the particle size of Cr3C2 is 5-10 μm, and the purity of each raw material powder is higher than 99.5%.
4. The method for preparing a (TiCrMoNbTa) C-based high entropy ceramic according to claim 2, characterized in that: The specific steps of step S1 are: S11: weighing each raw material powder according to an equal metal atomic ratio; S12: Put the raw material powder weighed in S11 into an agate ball mill with a ball-to-powder ratio of 10:1, seal the ball mill with vacuum silicone grease, and fill the ball mill with argon gas; S13: ball milling is performed using a planetary ball mill with a rotation speed of 240 r / min and a ball milling time of 10 h.
5. The method for preparing a (TiCrMoNbTa) C-based high entropy ceramic according to claim 4, characterized in that: The ratio of the raw material powders is TiC:NbC:Cr3C2:Mo2C:TaC=6:6:2:3:
6.
6. The method for preparing a (TiCrMoNbTa) C-based high entropy ceramic according to claim 2, characterized in that: The specific steps of step S2 are: S21: adding metal Ti powder with different molar contents to the obtained powder A; S22: The raw material powder weighed in S21 is placed into an agate ball mill with a ball-to-powder ratio of 10:1, the ball mill is sealed with vacuum silicone grease, and argon gas is filled into the ball mill; S23: ball milling is performed using a planetary ball mill with a rotation speed of 240 r / min and a ball milling time of 10 h.
7. The method for preparing a (TiCrMoNbTa) C-based high entropy ceramic according to claim 6, characterized in that: The raw material powders are proportioned according to different Ti contents, and respectively include raw material powders in the following molar ratios: 10% to 30% Ti, 14% to 18% TiC, 14% to 18% Mo2C, 14% to 18% NbC, 14% to 18% Cr3C2, and the rest is TaC.
8. The method for preparing a (TiCrTaNbMo)C-based high entropy ceramic according to claim 2, characterized in that: In step S3, the sintering pressure is 30 MPa and the vacuum degree is less than 1.8×10 -2 Pa.
9. The method for preparing a (TiCrMoNbTa) C-based high entropy ceramic according to claim 2, characterized in that: In step S3, the sintering temperature is 1650° C., the heating rate during the sintering process is 10° C. / min, and the holding time is 2 h.
Citation Information
Cited By
High-conductivity (TiTaNbCrMe) (N, C) high-entropy carbonitride ceramic material and preparation method thereof
CN121470959A
A transition metal involved high-entropy carbide ceramic composite material and a preparation method thereof
CN122809890A